Factors affecting the business success of small and medium food enterprises in the Philippines - Borazon, Elaine Quintana
Determines the factors that influence the business success of small and medium food enterprises in the Philippines. A survey of 233 food enterprises was conducted and structural equation modeling was used to test the hypotheses. Recommends also that cross-cultural research can also be done to develop a generalizable model for factors affecting the business success of small and medium enterprises.